On the role of receptor downregulation and costimulation in shaping the T cell response - Kruger, P (2018)
T cells are critical decision-makers in the immune system and their activation determines whether a cell or molecule constitutes a threat to the body and needs to be eliminated or whether it should be ignored and tolerated by the immune system. Many molecules that play a role in T cell activation and their interactions with each other have been identified, but an overall understanding of the decision-making processes that lead to changes in T cell behaviour remain enigmatic. We are studying human T cell activation through a combination of in vitro experimental stimulation experiments and mathematical modelling. Our minimal experimental platform allows us to systematically vary the input signals the T cell receives by modulating antigen dose, antigen affinity, stimulation time and costimulatory ligands, and by stimulating through either a TCR or a CAR. We show here that T cell activation (measured as cytokine production) shows an adaptation phenotype in response to all antigen doses and affinities. A detailed study of TCR downregulation and the incorporation into a mathematical model revealed that TCR downregulation is sufficient to explain this adaptation. The intrinsic inactivation of the T cells is contextdependent and the cells can be re-activated with a higher affinity ligand. Furthermore, we show that the inactivated cells can be re-activated when a non-stimulating pMHC is presented together with a costimulatory ligand. We generated a similar dataset for CAR T cells and showed that they can equally get desensitised by antigen and that the CAR is also downregulated depending on antigen dose and affinity, suggesting that a similar model may apply. We used the resulting mathematical model of T cell activation to predict the potential effects of costimulatory molecules on the dose response profiles, including, for example, adhesion effects or signal amplification. We then systematically stimulated T cells with ligands to CD2 and CD28 and compared the responses to the model predictions. We found that CD28 primarily lowers the threshold for T cell activation downstream of the TCR whereas CD2 showed a more complex phenotype with a strong adhesion effect combined with amplifying effects on downstream signalling.